Gun Violence Prevention 2.0: A New Framework for Addressing America’s Enduring Epidemic - Mike McLively (Washington University Journal of Law & Policy, 2019)
This article proposes solutions to move forward the national debates regarding guns, arguing that these conversations have felt frozen for many years. The article proposes reframing the issue from the perspectives of public health and human rights in order to help American society rethink the gun violence epidemic in a way that the article suggests would be truly transformative.
Keywords: gun violence; prevention; Gabby Giffords; gun violence epidemic; public health; human rights; reframe; debate